2017
DOI: 10.1101/234161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene networks underlying faster flowering induction in response to far-red light

Abstract: Light is one of the main signals that regulates flowering. Low red to far-red ratios accelerate flowering in a wide range of species. The central gene pathways controlling flowering time in Arabidopsis, appear to be largely conserved in legumes. However, numerous examples exist of gene duplication and loss. The role of CONSTANS-LIKE genes as integrators of the photoperiod response has been questioned in several dicot species, including legumes. In this study on subterranean clover, using RNA-seq and controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Another recent study with an annual subterranean clover ( Trifolium subterraneum L .) showed that several putative flowering‐promoting genes were upregulated under FR‐enriched light, such as orthologs of FLOWERING LOCUS T ( FT ) and CONSTANS ‐like ( COL ) genes (Pazos Navarro et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another recent study with an annual subterranean clover ( Trifolium subterraneum L .) showed that several putative flowering‐promoting genes were upregulated under FR‐enriched light, such as orthologs of FLOWERING LOCUS T ( FT ) and CONSTANS ‐like ( COL ) genes (Pazos Navarro et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Among others, they identified orthologs of PHYTOCHROME INTERACTING FACTOR 3 (PIF3) and B-BOX PROTEIN 19 (BBX19), alongside several heat-shock protein orthologs. Another recent study with an annual subterranean clover (Trifolium subterraneum L.) showed that several putative flowering-promoting genes were upregulated under FR-enriched light, such as orthologs of FLOWERING LOCUS T (FT) and CONSTANS-like (COL) genes (Pazos Navarro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This QTL was located at the beginning of chromosome 6 (Figures 2 and 4a) with a significant SNP in the 5′ untranslated region of the first of two lentil FTb ortholog genes located in tandem at the top of chromosome 6. FTb genes are known flowering time genes related to photoperiod response in several legumes including lentil (Hecht et al., 2011; Ortega et al., 2019; Pazos‐Navarro et al., 2018; Weller & Ortega, 2015; Yuan et al., 2021). In all these species, the expression of FTb genes show a strong long‐day requirement and therefore the effect of a FTb allele with (a) a mutation altering their expression pattern would be more relevant in short‐day environments (Mediterranean, southern Asia) or (b) a mutation impairing or enhancing its floral inductive capacity would be more evident in locations where photoperiodic requirements are met such as temperate environments.…”
Section: Resultsmentioning
confidence: 99%
“…This QTL was located at the beginning of chromosome 6 ( Figure 2, Figure 4a ), with a significant SNP in the 5’ UTR of the first of two lentil FTb orthologs genes located in tandem at the top of chromosome 6. FTb genes are known flowering time genes related to photoperiod response in several legumes, including lentil (24, 53, 56, 58, 59). In all these species, the expression of FTb genes show a strong long day requirement, and therefore the effect of a FTb allele (i) with a mutation altering their expression pattern would be more relevant in SD environments (Mediterranean, South Asian) or (ii) with a mutation impairing or enhancing its floral inductive capacity would be more evident in locations where photoperiodic requirements are met, such as temperate environments.…”
Section: Resultsmentioning
confidence: 99%